Science in the Schools--Some Homework To Be Done. - Lammel, Rose (Educational Leadership, 1962)
The article reports that science programs in the schools are greatly in need of change and improvement is scarcely news to anyone these days. An up-to-date, effective program of learning in science in any system does not develop by chance. Definite agreements and plans need to be evolved locally by all those concerned. The need for reviewing and rethinking the science program in the schools has been sharpened by the urgencies of life in the last half of this century. Social and cultural forces, accelerated in the past decade, have crowded us into this nationwide questioning of the adequacy of the school program in science. Many schools have teachers who have participated in many science projects in one way or another. The experience of these teachers should be utilized in improving the local school program. Other resources are at hand to be drawn upon. Through financial assistance made possible by the National Defense Education Act, local schools can improve materially the supply of tools and equipment for scientific inquiry needed by learners as they participate in quality programs of science